2013
DOI: 10.1039/c2lc40898h
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic probes for use in life sciences and medicine

Abstract: Microfluidic probes (MFPs) combine the concepts of microfluidics and of scanning probes and constitute a contact-free and channel-free microfluidic system. Whereas classically the sample is introduced into the microfluidic device, with a MFP, the microfluidic stream is applied to the sample. MFPs use hydrodynamic flow confinement instead of walls to constrain a microfluidic stream between the MFP tip and a substrate. Because MFPs are free to move, they can be used to process large areas and samples in a select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(42 citation statements)
references
References 69 publications
0
42
0
Order By: Relevance
“…More recently, stagnation flows have been developed with open microfluidic systems in the form of microfluidic pipettes and probes, to collect vesicles and perform cell analysis respectively . The microfluidic probe has been further developed to generate the microfluidic quadrupole trapping mechanism, which has been used to study neutrophil chemotaxis . Detailed reviews on the application of microfluidic quadrupoles can be found in ref.…”
Section: Microfluidic Systems For Single‐cell Manipulationmentioning
confidence: 99%
“…More recently, stagnation flows have been developed with open microfluidic systems in the form of microfluidic pipettes and probes, to collect vesicles and perform cell analysis respectively . The microfluidic probe has been further developed to generate the microfluidic quadrupole trapping mechanism, which has been used to study neutrophil chemotaxis . Detailed reviews on the application of microfluidic quadrupoles can be found in ref.…”
Section: Microfluidic Systems For Single‐cell Manipulationmentioning
confidence: 99%
“…Currently, a variety of ex vivo methods are used to assay cell-to-cell signaling, including localized mechanical [9,10], electrical [11], and biochemical stimulations [12]. Compared with high precision of mechanical and electrical stimulations, it is difficult to realize localized biochemical stimulations without interfering with adjacent contacting cells due to the rapid diffusion of small molecules and the small surface size of attached cells.…”
Section: Introductionmentioning
confidence: 99%
“…Microfluidic devices, which handle fluids with volumes typically ranging from microliters to picoliters, have spawned important applications in many research fields including biology, medicine, chemistry, and engineering sciences [15]. On these microscopic scales, the fluid behavior is primarily influenced by viscosity rather than inertia, and the ratio of surface area to volume becomes larger providing rapid heat and mass transfer [6].…”
Section: Introductionmentioning
confidence: 99%